Bacterial community shift is induced by dynamic environmental parameters in a changing coastal ecosystem (northern Adriatic, northeastern Mediterranean Sea) – a 2‐year time‐series study. (30th June 2014) - Tinta, T.; Vojvoda, J.; Mozetič, P.; Talaber, I.; Vodopivec, M.; Malfatti, F.; Turk, V.
Summary The potential link between the microbial dynamics and the environmental parameters was investigated in a semi‐enclosed and highly dynamic coastal system (Gulf of Trieste, northern Adriatic Sea, NE Mediterranean Sea). Our comprehensive 2‐year time‐series study showed that despite the shallowness of this area, there was a significant difference between the surface and the bottom bacterial community structure. The bottom bacterial community was more diverse than the surface one and influenced by sediment re‐suspension. The surface seawater temperature had a profound effect on bacterial productivity, while the bacterial community structure was more affected by freshwater‐borne nutrients and phytoplankton blooms. Phytoplankton blooms caused an increase of Gammaproteobacteria (Alteromonadaceae, SAR86 and Vibrionaceae) and shift in dominance from SAR11 to Rhodobacteraceae taxon at the surface. Our results propose the importance of the water mass movements as drivers of freshwater‐borne nutrients and of allochthonous microbial taxa. This study emphasizes the prediction power based on association networks analyses that are fed with long‐term measurements of microbial and environmental parameters. These interaction maps offer valuable insights into the response of marine ecosystem to climate‐ and anthropogenic‐driven stressors.